HUBUNGAN ANTARA KARAKTERISTIK TEKNOLOGI DENGAN KEMUNGKINAN USAHA KECIL UNTUK MENGADOPSI TI - Rahab . (Jurnal Bisnis dan Ekonomi, 2009)
The decision making process of information technology adoption is affected byinformation technology (IT) characteristics. The purpose of this research is examineeffect IT characteristics (relative advantage, relevance, complexity and perceived cost)A survey was conducted in Yogyakarta city by purposive sampling technique.The samples that are used to data analysing are 102 small business. Partial LeastSquares method was used to examine five research hypotheses. Research instrumensvalidity was measured by convergent validity and discriminant validity. Instrumentreliability was measured by cronbach’s alpha and composite reliability.This research shows that relative advantage, complexity and perceived costhave significantly effect to small businesses decision to adopt IT. On the other, relevancenot effect to small businesses decision to adopt IT. This study contributes to insight thatIT adoption is affected by relative advantage of IT, level of IT complexity and perceivedcost of IT investment.Key words: adoption, information technology, small businesses, technological inovation